Implementation Total Sanitation Based on First Community-Based Pillar at Public - Kisra, Kisra; Alamsyah, Teuku; Kiswanto, Kiswanto; Murdani, Ihsan; Wintah, Wintah (PT.Mantaya Idea Batara, 2024)
Defecation in Indonesia is quite a lot to be found and one of the regions of Indonesia that still performs open defecation is in one of Aceh Regency, namely Southwest Aceh Regency which applies latrines to the people of Tangan-Tangan Cut Village, Regency, Southwest Aceh which is still small. The purpose of this study is to determine the application of latrines in the people of Tangan-Tangan Cut Village related to income, community work and education of the people of Hand-Cut Village, Setia District, Regency, Southwest Aceh. The method carried out is quantitative research using. Rendom sampling type . The number of informants in the form of respondents in this study was 40 respondents from 356 populations in hand-cut villages. The sampling technique is to use the slovin formula. The results of this study found that the application of latrines in village communities with cut, sub-district, faithful has no relationship between education (P = 0.635), income (P = 0.071) work (P = 0.337) people with latrine ownership, the number of respondents who have implemented latrines is 17 respondents with a percentage of 42.5%, while there are 23 respondents with a percentage of 57.5% who do not have latrines. The results of this research are that most villagers do not apply latrines / do not have latrines in their homes.